2001
DOI: 10.1161/hc37t1.094780
|View full text |Cite
|
Sign up to set email alerts
|

Very Long-Term Results (More Than 20 Years) of Valve Repair With Carpentier's Techniques in Nonrheumatic Mitral Valve Insufficiency

Abstract: Background-Mitral valve repair is considered the gold standard in surgery of degenerative mitral valve insufficiency (MVI), but the long-term results (Ͼ20 years) are unknown. Methods and Results-We reviewed the first 162 consecutive patients who underwent mitral valve repair between 1970 and 1984 for MVI due to nonrheumatic disease. The cause of MVI was degenerative in 146 patients (90%) and bacterial endocarditis in 16 patients (10%). MVI was isolated or, in 18 cases, associated with tricuspid insufficiency. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
194
2
12

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(217 citation statements)
references
References 12 publications
9
194
2
12
Order By: Relevance
“…There is therefore no way of knowing the longterm survival outcomes of mitral valve surgery as currently practiced. Based on existing data, it appears that if surgery is undertaken before onset of symptoms and where left ventricular function is preserved, the life expectancy should be similar to that of the general population [15,35,36]. When significant symptoms of heart failure have developed (NYHA III-IV) before mitral valve surgery is undertaken, the long term survival is significantly reduced (Fig.…”
Section: Long Term Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…There is therefore no way of knowing the longterm survival outcomes of mitral valve surgery as currently practiced. Based on existing data, it appears that if surgery is undertaken before onset of symptoms and where left ventricular function is preserved, the life expectancy should be similar to that of the general population [15,35,36]. When significant symptoms of heart failure have developed (NYHA III-IV) before mitral valve surgery is undertaken, the long term survival is significantly reduced (Fig.…”
Section: Long Term Survivalmentioning
confidence: 99%
“…The longest term follow-up available is for conventional 'Carpentier' techniques. Braunberger and colleagues [36] reported in 2001 on the long term outcomes of 162 non-rheumatic patients (of whom 90% were degenerative) who underwent a Carpentier repair between 1970 and 1984. They observed that 97% of patients with posterior leaflet, 86% with anterior leaflet and 83% of patients with bileaflet prolapse were free of re-operation at 20 years (Fig.…”
Section: Long Term Survivalmentioning
confidence: 99%
“…Abb. 3 dargestellt, aufgeschlüsselt nach den Pathologien: Wird ein Prolaps des vorderen Segels oder beider Klappensegel behandelt, kommt es bei der Resect-Strategie zu deutlich mehr Reoperationen [11], als wenn eine reine Pathologie des hinteren Segels vorliegt. Bei der Respect-Strategie unter Verwendung von Gore-Tex ® -Loops ist die Häu-figkeit einer Reoperation dagegen unabhängig von der Segelpathologie [9].…”
Section: » Bei Der Respect-strategie Ist Die Häufigkeit Einer Reoperaunclassified
“…3 8 Freiheit von Reoperationen bei Patienten mit primärer Mitralklappeninsuffizienz nach Verwendung der Resect- [11] oder Respect-Technik [9], aufgeschlüsselt nach der Pathologie. BS Beide Segel vom Prolaps betroffen, HS hinteres Segel betroffen, VS vorderes Segel betroffen Abb.…”
Section: Introductionunclassified
“…Since few selected centers worldwide have introduced minimally invasive mitral valve surgery using femoral cannulation together with direct transthoracic or endovascular aortic cross clamping, this technique has become an alternative treatment option for non-infected, non-ischemic mitral disease [3][4][5][6]. Conventional mitral valve repair shows excellent long-term durability [7,8]. Carpentier started mitral repair in 1968, developing the widely used repair techniques including ring annuloplasty, and thus conventional mitral repair has been popular in cardiac surgery since the beginning of the 1990ies.…”
Section: Introductionmentioning
confidence: 99%